A HQ como ferramenta de multiletramentos na escola: reflexões sobre a implementação de uma sequência didática no estágio de iniciação à docência no Pibid - FARIAS, Samara de Brito (2022)
This work focuses on a didactic experience of teaching the textual genre comic book (HQ) developed during the internship of initiation to teaching carried out under the subproject “Interdisciplinary Practices of Literacy and Literacy in Elementary School”. This subproject was part of the Scholarship Program for Teaching Initiation (Pibid) in the version related to CAPES Notice No. of Pedagogy offered by UFPA in Capanema and the municipal school Profa. Mary Nativity. The central problem of the research translates into the following question: how to work the teaching of comics at school with a view to making students' multiliteracies viable? In this vein, the general objective is to discuss the results of the application of a didactic sequence for the teaching of the comic book genre as a multiliteracies activity at school; while the specific objectives aim to characterize the comic book genre, describe the teaching experience based on the methodological proposal of a didactic sequence for textual genres and reflect on the use of comics in the teaching of verbal and non-verbal language from the tools offered by the educational software Hagáquê. As for the methodology, it is a research with a qualitative approach that used methodological procedures suitable for field research. Data were collected through participant observation carried out in the locus class of the initiation to teaching internship at different times of implementation of the didactic sequence. The records were systematically recorded in a field diary and complemented with photographs captured on a cell phone, in order to illustrate the different moments of the focused experience. The research aims to contribute to the process of children's multiliteracies and encourage elementary school teachers to develop student connectivity with the digital world, seeking in technological devices ways to boost student learning. From an academic point of view, there is a commitment to give visibility to the didactic experiments provided in the context of Pibid, as well as to encourage work with textual genres during the literacy and multi-literacy process of students, in addition to suggesting activities to be developed in the laboratories of Computing. In addition, this work can also be an interesting reference material for elementary and high school students interested in knowing more about the comics and the tools of the Hagáquê educational software.